Semiotics of comic food: on the sense of food hilarity - Leone, Massimo (E|C, 2020)
Starting from the abundant semiotic literature on the comic, the article tries to answer the following questions: what are the occasions when we laugh about food, and what value does such humor have in circulating unwritten gastronomic policies? In particular, how do we laugh at veganism today? What are the possible socio-cultural causes? And the pragmatic effects? Finally, what relationship is there between the laughter of vegans and the laughter of other minorities, gastronomic (vegetarians, hallal, kosher) and not?